Counseling for Mothers on the Importance of Deworming Toddlers at Posyandu Lavenda, Kenali Besar Community Health Center, Jambi City - Mastikana, Indah; Nadya, Embun; Oktoviani, Ayu; Yanti, Yuliana Saputri; Rahayu, Ananda Suci; Febrianti, Rina (International Journal of Social Science and Community Service, 2025)
Soil-Transmitted Helminths (STH), commonly known as intestinal worms, are infections caused by helminths transmitted through contaminated soil. Factors contributing to STH include poor hygiene, non-compliance with deworming treatment, inadequate sanitation, and limited knowledge about STH. In Indonesia, helminth infections remain a significant public health issue, with prevalence rates ranging from 2.5% to 62%. According to the 2021 Indonesia Nutritional Status Survey by the Ministry of Health, the proportion of toddlers suffering from helminth infections is approximately 2.8%. The World Health Organization recommends periodic treatment (deworming or preventive chemotherapy) without prior individual diagnosis for all at-risk individuals in endemic areas. This activity aims to enhance community knowledge and to treat and prevent helminth infections caused by roundworms, hookworms, whipworms, and pinworms, which can impede children's growth at Posyandu Lavenda, Kenali Besar Community Health Center, Jambi City. The results indicated that all participants were highly enthusiastic and engaged during the counseling sessions, and local healthcare workers were very proactive in implementing preventive measures against helminth infections in children as early as possible.